Transcriptional regulation of the anti-inflammatory cytokine IL-10 in acquired immune cells - Kubo, Masato; Motomura, Yasutaka (Frontiers in Immunology, 2012)
Although the major role of the immune response is host defense from a wide range of potentially pathogenic microorganisms, excess immune responses can result in severe host damage. The host thus requires anti-inflammatory mechanisms to prevent reactivity to self. Interleukin-10 (IL-10) is a cytokine with broad anti-inflammatory properties involved in the pathogenesis of various diseases. IL-10 was originally described as a T helper (TH)2 derived cytokine, but further studies indicated that IL-10 is expressed not only by many cells of the adaptive immune system, including T and B cells, but also by the innate immune cells, including dendritic cells (DCs), macrophages, mast cells, and natural killer (NK) cells. In addition, IL-10 can be induced in TH1 and TH17 cells by chronic inflammation as a system of feedback regulation. In this review, we focus on the molecular mechanisms underlying IL10 gene expression in adaptive immune cells and summarize the recent progresses in epigenetic and transcriptional regulation of the IL10 gene. Understanding the transcriptional regulatory events may help in the development of new strategies to control inflammatory diseases.